Caligus zei Norman and T. Scott 1906 (Crustacea: Copepoda), with a revision of the appendages. - Oakley, C.L. (Parasitology, Cambridge, 1926)
Habitat and record. The animal under consideration, a copepod of the Family Caligidae, has up to the present received three notices: by Norman and T. Scott (1906), A. Scott (1907), and T. and A. Scott (1913). (For further particulars see References at end of this paper, p. 409.) Norman and Scott stated that “the specimens were taken forty years ago on the dory by Laughrin, and by him sent to A. M. N.” Consequently, the specimens were forty years old before they were described, which would, even in the absence of other reasons, excuse a little scepticism as to the description. Scott gives a bare record of capture, with a copy of Norman and Scott's diagrams. These diagrams and the original of Norman and Scott are republished by Scott and Scott with the addition of a few errors. Considering these facts, and also that no satisfactory description is given of the appendages of the male, or of the maxillae or swimming legs of the female, and that the animal is very common, occurring on nearly every dory, I feel that there is some justification for a further description.